VSR performance in the Chicago Wheat Futures Contract - Flavin, Adam (Kansas State University, 2011)
The Chicago wheat futures contract has received attention in recent years regarding non-convergence with SRW wheat cash prices. In 2009 the CME Group announced their decision to implement a market based mechanism to set daily storage rates at registered delivery locations for the Chicago wheat contract. The new market based mechanism is a variable storage rate (VSR) that monitors Chicago wheat futures spreads relative to financial full carry. The running average of the futures spread at the end of the contract observation period determines future changes to existing storage rates. The objective of this study is to determine whether or not the adoption of VSR mechanisms has had an impact on SRW wheat basis convergence in the Toledo, OH switching district. The Chicago wheat contract months that were studied using OLS regression models include July 2010, September 2010, December 2010, and March 2011. A final OLS regression model examining the cumulative data collected from these four contract months concludes the research. The explanatory variables used to study SRW wheat basis convergence in Toledo includes days to delivery, all wheat ending stocks as a percentage of use for the United States, and VSR. In two of the regression models for the contract months studied VSR found to have a statistically significant impact, i.e., the December 2010 and March 2011 models. In the cumulative regression model covering all four wheat contract months VSR was also found to have a statistically significant impact on SRW wheat basis convergence. The regression models in this analysis appear to contain some degree of multicollinearity, a statistical condition in which the explanatory variables tend to move collinearly or “together” with each other. Multicollinearity oftentimes can result in deceptively high and inconsistent statistical results in econometric models.
Keywords: Chicago Wheat Futures; Variable Storage Rate; Convergence; Carrying Cost; Wheat basis; Agriculture, General (0473); Economics, Commerce-Business (0505); Marketing (0338)